1959
DOI: 10.1146/annurev.ns.09.120159.001253
|View full text |Cite
|
Sign up to set email alerts
|

Solvent Extraction in Radiochemical Separations

Abstract: The last several years have seen a reawakening appreciation of the value of solvent extraction separations processes both on analytical and process scales. Separations by solvent extraction are simple, convenient, clean, and applicable equally well to carrier-free tracer and macro amounts of materials. They usually require apparatus as uncomplicated as a separatory funnel and may readily be adapted to remote handling procedures.A variety of separations techniques have been applied to the problems of isolation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1961
1961
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…It provides a high selectivity even when dealing with very low concentrations, as partition conditions can be easily varied to obtain radioisotope yields relatively free from chemical and radionuclidic impurities. LLE can be performed rapidly (a particularly vital characteristic when isolating isotopes with shorter half-lives), and is relatively simple to automate [61,63]. Typically, LLE is followed by evaporation of the extracting solvent, back extraction in aqueous phase or SPE/chromatography to purify the radionuclide from the organic phase and dissolved into a solution phase appropriate for successive radiolabelling or injection.…”
Section: Use Of Lle For Radioisotopes Productionmentioning
confidence: 99%
“…It provides a high selectivity even when dealing with very low concentrations, as partition conditions can be easily varied to obtain radioisotope yields relatively free from chemical and radionuclidic impurities. LLE can be performed rapidly (a particularly vital characteristic when isolating isotopes with shorter half-lives), and is relatively simple to automate [61,63]. Typically, LLE is followed by evaporation of the extracting solvent, back extraction in aqueous phase or SPE/chromatography to purify the radionuclide from the organic phase and dissolved into a solution phase appropriate for successive radiolabelling or injection.…”
Section: Use Of Lle For Radioisotopes Productionmentioning
confidence: 99%
“…The well-established 'PUREX' process uses tributyl phosphate (TBP) to sequester actinides against a background of metal cations. An early study indicated that the complexation of TBP to uranyl ion was more than to REE [46]. Hence, TBP was considered as a possible agent to retard removal of UO 2 2+ in the REE-accumulating column to enable later recovery of U(VI) downstream.…”
Section: Biotechnology Progress Towards Selective Recovery Of Ree: Usmentioning
confidence: 99%
“…A hypothesis was formulated to widen the flow rate 'window' boxed in Figure 3. This assumes that REE 3+ forms a weaker complex with TBP than does UO 2 2+ [46]; no benefit for REE removal would be anticipated with TBP (Figure 6) if REE 3+ is presumed to be not in close association with TBP or its breakdown products. Rare earth phosphate (REEPO 4 ) formation is rapid and hence occurs at high flow rates while UO 2 2+ requires more time to form a precipitate [21].…”
Section: Biotechnology Progress Towards Selective Recovery Of Ree: Usmentioning
confidence: 99%
“…According to the paper of H. FREISER ar~d G~ORr H. MORRISON [11], the following elements of the periodic system can be expected as partially extracted together with (UO2) + +: Zr, As, Ce(IV).…”
Section: Present Investigations On Mixed Fission Products A) Activatimentioning
confidence: 99%